1. (x-1)(x+2)=0
x²+x-2=0
D=b²-4ac=1²-4×1×(-2)=9
X1=-1-3/2=-2 X2=-1+3/2=1
2. X×(x+0,5)=0
x²+0,5x=0
D=0,25
X1=-0,5-0,5/2=-0,5 X2=-0,5+0,5/2=0
3. x²-2x=0
D=4
X1=2-2/2=0 X2=2+2/2=2
4. x²-16=0
(x-4)(x+4)=0
X1=4 X2=-4
5. 9x²-1
(3x-1)(3x+1)=0
X1=1/3 X2=-1/3
1. (x-1)(x+2)=0
x²+x-2=0
D=b²-4ac=1²-4×1×(-2)=9
X1=-1-3/2=-2 X2=-1+3/2=1
2. X×(x+0,5)=0
x²+0,5x=0
D=0,25
X1=-0,5-0,5/2=-0,5 X2=-0,5+0,5/2=0
3. x²-2x=0
D=4
X1=2-2/2=0 X2=2+2/2=2
4. x²-16=0
(x-4)(x+4)=0
X1=4 X2=-4
5. 9x²-1
(3x-1)(3x+1)=0
X1=1/3 X2=-1/3